2011
DOI: 10.1111/j.1753-4887.2011.00399.x
|View full text |Cite
|
Sign up to set email alerts
|

Beyond cholesterol-lowering effects of plant sterols: clinical and experimental evidence of anti-inflammatory properties

Abstract: Inflammation is a strong risk factor for cardiovascular disease. Dietary plant sterols are known to reduce plasma cholesterol levels and thereby reduce cardiovascular risk. Recent observations from animal and human studies have demonstrated anti-inflammatory effects of phytosterols. For example, several animal and human studies report reductions in the levels of proinflammatory cytokines, including C-reactive protein, after consumption of dietary plant sterols. Although the cholesterol-lowering effects of phyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
84
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(86 citation statements)
references
References 102 publications
2
84
0
Order By: Relevance
“…Dgat2 and Hepatic lipase were unchanged after PSE and PSA feeding (Table 3). To investigate a potential anti-infl ammatory effect of plant sterols/stanols, we also determined the expression of several hepatic proinfl ammatory genes ( 20 ). Interestingly, PSE/PSA treatments did not result in changes in the expression of any Plasma lipoprotein analysis.…”
Section: Plant Sterols and Plant Stanols Supplemented To Hfd Results mentioning
confidence: 99%
See 1 more Smart Citation
“…Dgat2 and Hepatic lipase were unchanged after PSE and PSA feeding (Table 3). To investigate a potential anti-infl ammatory effect of plant sterols/stanols, we also determined the expression of several hepatic proinfl ammatory genes ( 20 ). Interestingly, PSE/PSA treatments did not result in changes in the expression of any Plasma lipoprotein analysis.…”
Section: Plant Sterols and Plant Stanols Supplemented To Hfd Results mentioning
confidence: 99%
“…Because there is a potential link between hepatic infl ammation and VLDL production, we investigated whether plant sterols/stanols could also act as anti-infl ammatory agents, as has been previously suggested [for review see ( 20 )], and whether this could explain the decrease in hepatic VLDL production. We did not fi nd any differences in hepatic mRNA levels of several infl ammatory markers.…”
Section: Discussionmentioning
confidence: 99%
“…High levels of campesterol have been associated with signal quality (López & Martín, 2009; Martín & López, 2006a); (3) stigmasterol, a relatively common, but not abundant steroid that is believed to be acquired via ingestion of plants. This compound is associated with structural properties in secretions, as well as with healthy conditions (Othman & Moghadasian, 2011); (4) ergosterol (i.e., provitamin D 2 ), a common steroid that acts as a metabolic precursor of vitamin D 2 , and believed to offer a reliable indicator of male healthy condition. Therefore, this compound has been seen to play a key role in mate choice (Martín & López, 2006c, 2008), making in particularly interesting given the difficulties to demonstrate mate choice in lizards based on quantitative traits (Olsson et al., 1998); (5) 9,12‐octadecadienoic acid (i.e., linoleic acid) is a unsaturated fatty acid, costly to obtain.…”
Section: Methodsmentioning
confidence: 99%
“…The presence of phytosterols like campesterols exhibits its anti-inflammatory nature (Othman and Moghadasian 2011). From the above discussion, it has been revealed that EEBL potentially inhibits the inflammatory factors in IBD and alleviates the symptoms in IBD.…”
Section: Discussionmentioning
confidence: 98%